2010
DOI: 10.1371/journal.pntd.0000616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxfendazole, Praziquantel and Albendazole against Cystic Echinococcosis: A Randomized Clinical Trial in Naturally Infected Sheep

Abstract: BackgroundCystic Echinococosis (CE) is a zoonotic disease caused by larval stage Echinococcus granulosus. We determined the effects of high dose of Oxfendazole (OXF), combination Oxfendazole/Praziquantel (PZQ), and combination Albendazole (ABZ)/Praziquantel against CE in sheep.Methodology/Principal FindingsA randomized placebo-controlled trial was carried out on 118 randomly selected ewes. They were randomly assigned to one of the following groups: 1) placebo; 2) OXF 60 mg/Kg of body weight (BW) weekly for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Although there are no comparative randomized studies exploring treatment with albendazole in monotherapy versus combined therapy with albendazole plus praziquantel in patients without surgery, it appears that the combined therapy could improve the results obtained with albendazole alone. 17,18,[23][24][25][26]38 In addition, treatment with praziquantel plus albendazole before surgery could be more efficient as regards reducing relapse rates in comparison with albendazole monotherapy. 23 To date, there are no published randomized clinical trials comparing both therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no comparative randomized studies exploring treatment with albendazole in monotherapy versus combined therapy with albendazole plus praziquantel in patients without surgery, it appears that the combined therapy could improve the results obtained with albendazole alone. 17,18,[23][24][25][26]38 In addition, treatment with praziquantel plus albendazole before surgery could be more efficient as regards reducing relapse rates in comparison with albendazole monotherapy. 23 To date, there are no published randomized clinical trials comparing both therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalez and others 16 showed that oxfendazole is effective against T. solium cysticercosis in naturally infected pigs. Likewise, Gavidia and others 15 showed that oxfendazole in combination with praziquantel is effective against hydatid disease (Echinococcus granulosus) in naturally infected sheep. Oxfendazole has also been previously used for the treatment of fascioliasis.…”
Section: Discussionmentioning
confidence: 97%
“…The control group did not receive treatment, whereas the treatment group was treated orally with a single dose of 30 mg/kg of body weight of oxfendazole (Synanthic, Fort Dodge, Mexico), adapted from the studies from Gavidia and others 15 and Gonzalez and others. 16 A drench dosing gun was used for oxfendazole administration, with the animal in standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Eosin (0.1%) has been frequently used for the in vitro viability test of protoscolices of hydatid cyst by many researchers (Diker et al 2007;Ciftci et al 2007;Esme et al 2007;Moazeni and Larki 2010;Gavidia et al 2010;Moazeni and Nazer 2010;Moazeni and AlipourChaharmahali 2011). They have exposed the protoscolices to 0.1% eosin for 15 min, however we obtained the best results after 30 min of exposure time.…”
Section: Discussionmentioning
confidence: 99%